1994
DOI: 10.1346/ccmn.1994.0420406
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Nuclear Magnetic Resonance Spectroscopy on Synthetic Ammonium/Aluminum-Saponites

Abstract: Abstract--Ammonium-saponite is hydrothermally grown at temperatures below 300~ from a gel with an overall composition corresponding to (NH4)o.6Mg3Alo.,Sia.4Ot0(OH)2. Using 27A1 and 29Si solid-state Magic Angle Spinning NMR techniques it is demonstrated that synthetic ammonium-saponites have a rather constant Si/A1 Iv ratio (~5.5) and an AFV/A1 vl ratio that varies between 1.5 and 3.8. The above ratios are independent of the synthesis temperature, although an increasing amount of Si, I'4, and, to a lesser exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 10 publications
1
25
1
1
Order By: Relevance
“…For this reason, different methods have been developed to prepare synthetic saponites with well-controlled chemical composition and property (Farmer et al 1991(Farmer et al , 1994Kloprogge et al 1993Kloprogge et al , 1994aKloprogge et al , 1994bVogels et al 1997Vogels et al , 2005bKawi and Yao 1999;Yao et al 2005;Higashi et al 2007;Bisio et al 2008;Vicente et al 2010;Xue and Pinnavaia 2010). For instance, Farmer et al (1991Farmer et al ( , 1994 synthesized well-formed saponite in hydrazine-water mixtures and found that the presence of Fe 2+ in a calcareous environment may promote the formation of saponite.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, different methods have been developed to prepare synthetic saponites with well-controlled chemical composition and property (Farmer et al 1991(Farmer et al , 1994Kloprogge et al 1993Kloprogge et al , 1994aKloprogge et al , 1994bVogels et al 1997Vogels et al , 2005bKawi and Yao 1999;Yao et al 2005;Higashi et al 2007;Bisio et al 2008;Vicente et al 2010;Xue and Pinnavaia 2010). For instance, Farmer et al (1991Farmer et al ( , 1994 synthesized well-formed saponite in hydrazine-water mixtures and found that the presence of Fe 2+ in a calcareous environment may promote the formation of saponite.…”
Section: +mentioning
confidence: 99%
“…In this respect, Kloprogge and co-workers have conducted a series of investigations during the last two decades, by using a combination of various characterization techniques (Kloprogge et al 1993(Kloprogge et al , 1994a(Kloprogge et al , 1994bVogels et al 1997Vogels et al , 2005b. Al ions could occupy both tetrahedral and octahedral sites and the Al(IV)/ Al(VI) ratio increased with increasing synthesis temperature (Kloprogge et al 1994a(Kloprogge et al 1994b.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…The range of different sites for Mg 2+ and A13+ prevents control of the composition and the layer charge of the composites during synthesis as demonstrated by Kloprogge et al (1993aKloprogge et al ( , 1994aKloprogge et al ( , 1994b and Vogels et al (1995). Harder (1972) claimed to have synthesized trioctahedral smectite (i.e., saponite) from Mg-containing Al(OH)3-silica precipitates at 20~…”
Section: Saponitementioning
confidence: 99%
“…Even in monometallic systems (e.g., Fe) a wide range of hydroxide, oxide, or oxyhydroxide Neumann (1971Neumann ( , 1972, Neumann and Sansom (1976) Torii et al (1983), Torii (1985, Iwasaki (1986, 1987) Roy (1963a, 1963b) 800~ 24 h; 850~ 2 Li-fluorhectorite, h Na~CO3, Li2CO 3 silica sand, MgO, 925~ Na2CO3, Na2SiF6 Mg-, AI-, Na-nitrates, Sil-mostly -<575~ and 1 saponite ica sol (Ludox) kbar, some syntheses at 600-900~ or > 1 kbar quartz, Li2SiO3, fluoramphiboles fluorhectorite Hickson (1974Hickson ( , 1975 hydrous silica sol, AI(OH)3, Mg(OH)2 NH4OH or NH4F Granquist (1966), Kuchta hydrous oxides of Si, A1, and Fajnor (1988) Mg, and Na Cohen et aL (1980) igneous rocks Suquet et al (1977Suquet et al ( , 1981aSuquet et al ( , 1981b, Hamilton and Henderson (1968), Booij (1992) Breukelaar et aL (1989, Kloprogge et al (1993aKloprogge et al ( , 1994aKloprogge et al ( , 1994b Noll (1936) kaolin, H4SiO4, Na-, K-, Ca-hydroxides Sand et al (1953Sand et al ( , 1957 Eberl and Hower (1977), Eberl (1978) De Kimpe (1976) Granquist (1966), Capell and Granquist (1966), Jaffe (1974), Gaaf et al (1983, R6bschl~i-ger et al (1984R6bschl~i-ger et al ( ), van Santen et al (1985, Heinerman (1985) Komarneni and Roy (1983), Komarneni and Breval (1985…”
Section: Synthetic Approachesmentioning
confidence: 99%